The call and rise of disability leaders in Uganda: The first Christian-based bachelors program in disability studies and special education at Africa Renewal University - Ashley A Hall (Health for All Nations, 2015)
This paper investigates the epidemic that prevails in the lives of persons and families affected by disabilities in developing countries, mainly East Africa and Uganda. Grating data and demography are exposed, along with some of the common dilemmas found in the Ugandan educational systems, churches, and communities, in order to express the palpable realities of families and persons with disabilities. Patrons will discover the features and attributes that constructs the disability studies and special education bachelor's program at Africa Renewal University, including course listings and course content, and how this program seeks to alleviate some of the major wounds for persons and families affected by disabilities in East Africa, which all contribute to identifying the problem and bringing forth resolution. Lastly, this paper highlights bouyant outcomes, strategies for moving forward, and a scope of the next steps for Christlike front-runners and the souls affected by disabilities subsiding in Uganda and East Africa.